1970
DOI: 10.1364/ao.9.000385
|View full text |Cite
|
Sign up to set email alerts
|

A Ray Analysis of Optical Resonators Formed by Two Spherical Mirrors

Abstract: A paraxial resonance equation is derived. This gives the mirror separation as a function of the radii of curvature of the mirrors and an integer N which is the number of return transits necessary to form a closed path of rays. Differentiating the paraxial resonance equation gives a formula for the relative mode density as a function of mirror separation. It is shown that the output power from a laser incorporating solid mirrors is inversely proportional to the mode density. In the case of hole coupling, the ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
1

Year Published

1972
1972
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 14 publications
3
49
1
Order By: Relevance
“…The parameters of resonators where beats are lacking in Fig. 7a conform with the condition of paraxial resonance derived in the context of resonator described by the methods of geometric optics [9]:…”
Section: B Oscillation Period and The Character Of Field Amplitude Esupporting
confidence: 67%
See 3 more Smart Citations
“…The parameters of resonators where beats are lacking in Fig. 7a conform with the condition of paraxial resonance derived in the context of resonator described by the methods of geometric optics [9]:…”
Section: B Oscillation Period and The Character Of Field Amplitude Esupporting
confidence: 67%
“…The evolution of the relaxation oscillation amplitude can be aperiodic or occur as beating. The wave-based resonator simulation reveals "paraxial resonances" predicted in [9] by the methods of ray optics. It has been shown that the conditions of paraxial resonance are matched by aperiodic processes of evolution of relaxation oscillation amplitude in the course of mode formation.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Many other techniques have also been proposed to increase the resolution and measurement speed of the conventional on-axis CRDS technique, such as: laser-locked CRDS system [14], fast frequency scanning of the laser [15], rapidly swept cavity design [16], or a combination of the cavity modulation and fast laser scanning approaches [17]. This paper reports off-axis light injection with re-entrant configuration [18,19] of the ring-down cavity has been used. The off-axis technique provides enhancement of the spectral resolution without cavity length modulation [10,20,21].…”
mentioning
confidence: 99%